The environmental and social cost of the urban mobility system in the metropolitan area of Lima - Conto Quispe, Zulema (2018)
The article demonstrate the environmental and social cost the urban mobility system in the Metropolitan Area of Lima. The methodological design is exploratory and descriptive, for which a quantitative and qualitative secondary data source is used. The article shows that the higher environmental costs of the urban transport system area associated with the high consumption of non-renewable resources; and in the social costs, motorized vehicles overlap citizens.